PELAKSANAAN DISKRESI APARATUR SIPIL NEGARA DALAM RANGKA PENEGAKAN HUKUM - Rossi Suparman (Universitas Suryakancana, 2020)
Secreted as an action or decision that can be used by the state civil service (ASN) under certain conditions, in carrying out the law enforcement duties of civil servants especially the police the authority to use discretion can be applied according to the conditions needed in the context of law enforcement, but after the enactment of Law Number 30 of 2014 concerning Government Administration requires clarity regarding the position of discretion in law enforcement. The method used is a normative approach using secondary and primary data that is analyzed qualitatively. The results showed (1) That the enactment of the Law on Government Administration is an effort to provide a legal position for discretion within the State Civil Apparatus. Discretion is regulated more clearly, from the definition, the limit according to the law, the limit is issued by the authorized official, the purpose, scope, conditions, use of discretion and approval procedures, and the consequences of discretionary law. (2) POLRI in its position as a law enforcement apparatus has the function of enforcing law in the judicial field both preventive and repressive. So with the discretionary authority in the judicial field as stipulated in Law No. 2 of 2002 in Article 18 paragraph (1) that